DEVELOPING A WEB-BASES SYSTEM OF BENGKULU TOURIST - Ali Ibrahim (Jurnal Sistem Informasi, 2009)
One of the main programs of local government of Bengkulu city is tourism sector development. One of its main activities is to promote tourism objects. Internet technology is one of the ideal channel and a powerful tool to promote tourism with a very low cost. By this technology, it can provide information in a web form, so the users will easily find information such as several options of attractive tourist destination places and supporting the existing facilities at each tourist attraction. Results from testing respondents obtained 19% strongly agreed, 55% agreed, 16% neutral and 10% disagreed. With this result, we can conclude that the system can help the local government of Bengkulu city in promoting its tourism objects. In addition, this system can also be useful as informative inputs for investors who want to develop a specific tourist attraction. The expected impact of this system is the number of tourists visiting the city of Bengkulu significantly increased. Â  Keywords: tourism information system, php, MySQL, web-based, open source.